Digital twin-enabled interactive cockpits for smart products management and testing - Rachamim, Matti; Hornik, Jacob (Frontiers in Artificial Intelligence, 2025)
Digitalization is influencing the design, development, and management of products across myriad industries, transforming traditional products into smart ones. Among digital technologies and models, the digital twin (DT) is regarded as an important contribution to the advancement of physical entity management. DTs are virtual representations of physical objects or systems, which are continuously updated with real-time data collected from their physical counterparts. Surprisingly, DT has yet to be applied in marketing. This study aims, accordingly, first, to introduce the DT concept and, second, to explore the human factor (human-in-the-loop) in DT. Third, elaborate on the DT cockpit (the DT’s interactive element) in the product management paradigm. Specifically, the authors use vehicles as a case study to show how interactive digital twins (IDTs) can be employed to predict and optimize vehicle performance, reliability, sustainability, and customer satisfaction. To conceptualize IDT for smart products and marketing analytics, the customer-centric Technology Acceptance Model (TAM) is employed. As this is the first study to explore DT technology in marketing, the DT concept’s main attributes are discussed, significant contributions are suggested, and avenues for future research are delineated.